PENGARUH PRODUK DOMESTIK BRUTO NEGARA INDONESIA, UKURAN PERUSAHAAN DAN DIVIDEN PAYOUT RATIO PADA RETURN SAHAM - Putra, I Nyoman Sutrisna Adi; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2016)
Investors in investing always consider factors that affect the price of shares purchased. This study aims to determine the effect of the Gross Domestic Product, Company Size and Dividend Payout Ratio Stock Return manufacturing companies including LQ 45 index on the Stock Exchange. This study uses a quantitative approach in the form of associative. The population in this study were taking 83 companies in the index LQ 45. Engineering sampling using purposive sampling technique. The sample in this study were taking 12 manufacturing companies whose shares remain listed in the LQ 45 years 2011 - 2014. In this new study used multiple linear analysis techniques. The results showed gross domestic product has no effect on Stock Return, while the size of the Company and Dividend Payout Ratio positive effect on stock returns.
Keywords: GDP, Company Size, Dividend Payout Ratio, Return Shares